Epidemiology of High Fertility Status among Women of Reproductive Age in Wonago District, Gedeo Zone, Southern Ethiopia: A Community-Based Cross-Sectional Study - Reda, Medhin Girmay; Bune, Girma Tenkolu; Shaka, Mohammed Feyisso (International Journal of Reproductive Medicine, 2020)
Background. High fertility remains one of the most important public health issues hampering the health and welfare of mothers and the survival of their children in developing nations. In Ethiopia, the high fertility rate has been seen for a long historical period with some pocket areas of high fertility still showing poor improvement. Hence, this study was aimed at determining the magnitude of high fertility status (number of children ever born alive≥5) and associated factors among women of the reproductive age group in Wonago district. Methods. A community-based cross-sectional study was conducted on randomly selected 512 women in Wonago district. Data were collected using a pretested structured interviewer administered questionnaire. Data was entered into EpiData version 3.1 and then analyzed by SPSS version 25. Logistic regression was used to analyze the data, and the adjusted odds ratio with the 95% confidence interval was computed, and a significant association was declared at p value ≤ 0.05. Result. This study revealed that 354 (69.1%) of the respondents have high fertility. High fertility is independently associated with residing in rural area [AOR=4.88, 95% CI: 3.21, 7.86], desire for children [AOR=6.97, 95% CI: 3.24, 11.40], history of under-five child mortality [AOR =5.32, 95% CI: 2.59, 8.43], poor knowledge of contraception [AOR=2.67, 95% CI: 1.66, 4.04], and low wealth tertile [AOR=2.21, 95% CI: 1.51, 3.58]. On the other hand, women with age at first birth above 18 years [AOR=0.34, 95% CI: 0.17, 0.68] and those with birth interval≥24 months [AOR=0, 26, 95% CI: 0.14, 0.49] were less likely to have high fertility. Conclusion and Recommendation. The substantial number of women in the study area has high fertility status far away from the country’s costed implementation plan of reducing the total fertility rate to 3.0. Considering these, much is needed to be done among poor, rural residents, who have not yet attained their desired number of children, and on enhancing the knowledge of mothers towards contraceptive methods.